Analyzing Grammatical Errors in Students’ Theses at PGRI Silampari University Using Grammarly Premium - Desty Candriati Desty; Maria Ramasari; Ani Fiani (Universitas Sarjanawiyata Tamansiswa, 2026)
This research aimed to analyze grammatical errors found in the background sections of theses written by English Education Study Program students at PGRI Silampari University who graduated in 2024. The study employed a qualitative descriptive method with primary data consisting of 34 background sections collected through purposive sampling. To identify the errors, the Grammarly Premium application was used as an automatic detection tool. The analysis revealed a total of 526 grammatical errors. The most frequent errors occurred in the use of determiners, incorrect verb forms, and incorrect noun numbers. These findings suggest that students continue to face challenges in mastering fundamental aspects of English grammar, particularly in areas that impact sentence accuracy and clarity. This study is expected to contribute to academic evaluation by highlighting common grammatical weaknesses in student writing. Moreover, the results may serve as valuable input for lecturers and curriculum developers in designing effective teaching strategies to improve students' writing skills in academic contexts.